STARATEGI PENGEMBANGAN EKONOMI KREATIF DESA WISATA UNGGA KECAMATAN PRAYA BARAT DAYA KABUPATEN LOMBOK TENGAH - Muhamad Syafiq Rapiqi; Mahsun Mahsun; Lalu Masyhudi; Mumun Surahman (Journal Of Responsible Tourism, 2023)
This study discusses the creative economy devlopmen strategy in ungga vilage praya district soutwest distric central lombok. So that the purpose of this research is to provide a desciption of the potential of the creative economy in ungga vilage southwest praya subdistrict central lombok regency and to formulation the offorts made to the creative economy devlopment strategy in ungga vilage soutwest praya subdistrict central lombok regency. This study uses a qualitative desctiptive approach with date clolection techniques in the form of observation. Interviews, documentation and questionnaires. Data analiysis technique using SWOT analysis. The results show the SO (strenght-opportunity) and WO (weaknesses-opportunity) strategies namely by utilizing all the strnght factors possessed by the creative economy potential of the vilage of ungga to get the opportunities it has. and the ST (strength-threat) and WO (weaknesses-threat) strategies which are to make the marketing targets clearer by utilizing the tecnology that is currently developing. This can be done with solutions to improve marketing strategies through social media that are packaged attractively so that tourist want to make crafts as interesting gifts. The government provides training education and socialization to craftsmen and the community regarding the resilience of the creative economy potential.